'Blowing the whistle': the ethical, professional and legal implications of raising concerns and self‐regulation within dentistry. (11th October 2017) - Holden, ACL
Abstract: 'Whistle‐blowers' are a necessary part of any system; dentistry is no different. The role of whistle‐blowers in dentistry has been enshrined in Australian law since 2010. Raising concerns has become a legal duty as well as an ethical and professional obligation. It is important that these different aspects of raising concerns are explored as each adds another layer of consideration to the issue. The health professional's duty to whistle‐blow could be viewed as problematic; the observance of this duty is associated with being 'trapped between a rock and a hard place' where any decision to engage or not may have negative consequences. For the obligation of raising concerns to gain acceptability within the dental profession, the concept requires reframing as being necessary for the profession's continued success. The stigma of mandatory reporting needs to be removed to allow this essential process to occur. This article will discuss the ethical, professional and legal imperatives for the dental profession to engage with whistle‐blowing and the likely challenges that are likely to be met in doing so.